(untitled) - Norberg-Schulz, Christian (New York, 1986)
These eloquent essays provide a valuable history of the relationship between man and architecture in terms accessible to the lay reader yet challenging for specialists. Noted architectural critic and theorist Norberg-Schulz (The Concept of Dwelling et al.) points to a modern crisis of man's alienation from his surroundings, advocating a "phenomenology of our everyday environment.
Keywords: Architecture,Kiến trúc